Drivers of above‐ground understorey biomass and nutrient stocks in temperate deciduous forests. (11th December 2019) - Landuyt, Dries; Maes, Sybryn L.; Depauw, Leen; Ampoorter, Evy; Blondeel, Haben; Perring, Michael P.; Brūmelis, Guntis; Brunet, Jörg; Decocq, Guillaume; den Ouden, Jan; Härdtle, Werner; Hédl, Radim; et al.
Abstract: The understorey in temperate forests can play an important functional role, depending on its biomass and functional characteristics. While it is known that local soil and stand characteristics largely determine the biomass of the understorey, less is known about the role of global change. Global change can directly affect understorey biomass, but also indirectly by modifying the overstorey, local resource availability and growing conditions at the forest floor. In this observational study across Europe, we aim at disentangling the impact of global‐change drivers on understorey biomass and nutrient stocks, from the impact of overstorey characteristics and local site conditions. Using piecewise structural equation modelling, we determine the main drivers of understorey biomass and nutrient stocks in these forests and examine potential direct and indirect effects of global‐change drivers. Tree cover, tree litter quality and differences in former land use were the main drivers of understorey biomass and nutrient stocks, via their influence on understorey light and nitrogen availability and soil acidity. Other global‐change drivers, including climate and nitrogen deposition, had similar indirect effects, but these were either weak or only affecting nutrient concentrations, not stocks. Synthesis. We found that direct effects of global‐change drivers on understorey biomass and nutrient stocks were absent. The indirect effects of global change, through influencing resource availability and growing conditions at the forest floor, were found to be less important than the effects of overstorey cover and composition. These results suggest that understorey biomass and nutrient stocks might respond less to global change in the presence of a dense overstorey, highlighting the buffering role of the overstorey in temperate forests. Abstract : We found that direct effects of global‐change drivers on understorey biomass and nutrient stocks were absent. The indirect effects of global change, through influencing resource availability and growing conditions at the forest floor, were found to be less important than the effects of overstorey cover and composition. These results suggest that understorey biomass and nutrient stocks might respond less to global change in the presence of a dense overstorey, highlighting the buffering role of the overstorey in temperate forests.